Feasibility and safety of left bundle branch area pacing for patients with stable coronary artery disease - Shan, Yu; Lin, Maoning; Sheng, Xia; Zhang, Jiefang; Sun, Yaxun; Fu, Guosheng; Wang, Min (Frontiers in Cardiovascular Medicine, 2023)
Aims: Stable coronary artery disease (CAD) is a prevalent comorbidity among patients requiring pacemaker implantation. This comorbidity may have an impact on the safety and prognosis of traditional right ventricular pacing (RVP). Left bundle branch area pacing (LBBaP) is a new physiological pacing modality. Our aim was to investigate the feasibility and safety of LBBaP in patients with the stable CAD. Methods: This study included 309 patients with symptomatic bradycardia who underwent LBBaP from September 2017 to October 2021. We included 104 patients with stable CAD (CAD group) and 205 patients without CAD (non-CAD group). Additionally, 153 stable CAD patients underwent RVP, and 64 stable CAD patients underwent His-bundle pacing (HBP) were also enrolled in this study. The safety and prognosis of LBBaP was assessed by comparing pacing parameters, procedure-related complications, and clinical events. Results: During a follow-up period of 17.4 ± 5.3 months, the safety assessment revealed that the overall rates of procedure-related complications were similar between the stable CAD group and the non-CAD group (7.7% vs 3.9%). Likewise, similar rates of heart failure hospitalization (HFH) (4.8% vs. 3.4%, stable CAD vs. non-CAD) and the primary composite outcome including death due to cardiovascular disease, HFH, or the necessity for upgrading to biventricular pacing (6.7% vs. 3.9%, stable CAD vs. non-CAD), were observed. In stable CAD patients, LBBaP demonstrated lower pacing thresholds and higher R wave amplitudes when compared to HBP. Additionally, LBBaP also had significantly lower occurrences of the primary composite outcome (6.7% vs. 19.6%, P = 0.003) and HFH (4.8% vs. 13.1%, P = 0.031) than RVP in stable CAD patients, particularly among patients with the higher ventricular pacing (VP) burden (> 20% and > 40%). Conclusion: Compared with non-CAD patients, LBBaP was found to be attainable in stable CAD patients and exhibited comparable mid-term safety and prognosis. Furthermore, in the stable CAD population, LBBaP has demonstrated more stable pacing parameters than HBP, and better prognostic outcomes compared to RVP.